Selective Venous Blood Sampling for Hyperparathyroidism with unclear Localization of the Parathyroid Gland - Hader, Christopher; Uder, Michael; Loose, R. W. R.; Linnemann, U.; Bertsch, T.; Adamus, R. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: Evaluation of the benefit of selective venous blood sampling (SVS) for the preoperative identification of parathyroid adenomas with unclear localization in non-invasive diagnostics. Materials and Methods: In a retrospective study, all patients (n = 23) with primary (n = 21) or tertiary (n = 2) hyperparathyroidism were evaluated from 2005 to 2016 at the Hospital Nuremberg-North. These patients all received one (n = 20) or more (n = 3) SVS. 15 patients had one or more previous unsuccessful surgeries (group A), 8 patients received the SVS primarily before the first surgery (group B). Results of SVS were compared with the results of surgery, non-invasive diagnostic procedures and clinical follow up. Results: In 24 out of 26 SVS a significant PTH peak was found. 19 patients underwent surgery after SVS. In 16 of these cases (84 %) the SVS peak was concordant with the intraoperative localization. Thus, SVS of all operated patients had a sensitivity of 94 %. Considering only patients with prior HPT surgery the sensitivity was 89 %. In none of the 26 examinations complications occurred. Conclusion: Our results demonstrate that selective venous blood sampling SVS in cases with unclear imaging of parathyroid adenomas is an effective and low-risk invasive diagnostic method to localize parathyroid adenomas and helps to improve surgical therapy. Key points: o?low risk invasive diagnostic procedure to localize parathyroid adenomaso?additional step if non-invasive diagnostics are negative or inconclusiveo?high sensitivity in the detection of parathyroid adenomas Citation Format: o?Hader C, Uder M, Loose RWR et al. Selective Venous Blood Sampling for Hyperparathyroidism with unclear Localization of the Parathyroid Gland. Fortschr Röntgenstr 2016; 188: 1144 - 1150.
EVALuna2:14609